The development and farming of oyster mushrooms (Pleurotus ostreatus) and its connection to self-employment economic strategies: A Review (International Journal of Food and Nutritional Sciences, 2022)
This study investigates the relationship between self-employment economic methods and oyster mushroom growing (Pleurotus ostreatus). It looks at every stage of oyster mushroom development, from preparing the substrate to harvesting methods. The study looks at the financial effects of doing oyster mushroom farming as a side business, emphasizing how flexible and scalable it is. Policymakers, businesspeople and agriculture enthusiasts may use the findings to better understand how oyster mushrooms can be used to boost the economy, support sustainable development, and give people more options for self-employment. Additionally, mushroom cultivation and production was addressed as well as challenges associated with mushroom farming and an assessment of their nutritional content compared to other food consumed by humans. There is a dearth of knowledge in this area of great natural biodiversity, thus more research on the applications of mushrooms should be done in Drought areas of the nations.